Experimental study and modelling of the effect of microstructure on friction and wear mechanisms of low alloy steel. (15th December 2017) - Trevisiol, C; Jourani, A; Bouvier, S
Abstract: Few models are focused on the combined effects of microstructure and roughness on the tribological behavior of materials. Hardness is the material property mainly used in the tribological models which are usually at a macroscopic scale. For a dual-phase steel, experimental and predicted values of friction coefficients and specific wear resistances are compared. The investigated models are declined into two pressure distribution modes between the phases. Friction tests are performed between steel pins composed of a ferrite-martensite dual-phase microstructure against abrasive papers with various abrasive particle sizes ranging from 15 µ m to 200 µ m. By using heat treatments on a low alloy steel, dual-phase microstructures with various martensite volume fractions, ranging from 45% to 100%, are generated. As martensite volume fraction increases, the experimental and predicted results show that the specific wear resistance increases whereas the friction coefficient decreases. Furthermore, the latter evolutions depend on roughness. For a predominance of abrasive wear mechanisms generated by coarse abrasive particles (~200 µ m), the experimental tribological parameters tend to follow the predicted ones associated to the mode characterized by equal pressures between the phases. Then, as the abrasive particle size decreases, abrasive wear mechanisms reduce whereas adhesive wear mechanisms increase and the experimental tribological parameters tend to follow the predicted ones associated to the mode characterized by equal wear rate between the phases.